IMPLEMENTASI PERKEMBANGAN PEMIKIRAN EKONOMI SYARIAH DALAM MEWUJUDKAN LEMBAGA PERBANKAN SYARIAH DI INDONESIA - Kusuma, Nurul Rahmah; Hakim, Atang Abdul; Suherli, Ian Rakhmawan (Ahkam: Jurnal Hukum Islam, 2023)
The rapid development of Indonesian sharia banking institutions is marked by a change in the paradigm of capitalism towards a paradigm of religiosity and collaboration of thought by ulama, intellectuals, Muslim entrepreneurs, and the needs of society regarding the importance of implementing economics in accordance with Islamic principles. The aim of this research is to clarify sharia economic thinking in creating sharia banking institutions in Indonesia. This research method uses a qualitative library research approach, in the form of a library study sourced from secondary data, consisting of a collection of theories, books and research results related to sharia economic thinking and the formation of sharia banking institutions. The research results show that the formation of Indonesian sharia banking institutions exists to answer the problems faced by the Muslim community related to the phenomenon of usury in the banking sector. based on sharia economic thinking, sharia banking institutions were formed to achieve benefits, namely fulfilling the goals of maqashid sharia including fulfilling religion, soul, reason, lineage and property, and in implementing the concept it is the result of the IDB mainstream school, where sharia banking institutions emerged when This is by modern economic developments which are then modified to conform to Islamic principles.